A new species of Impatiens (Balsaminaceae) from southeastern Xizang, China - Yuan, Tao-Hua; Hu, Tian; Zhang, Bei; Cao, Ming; Du, Zhi; Chen, Xiang-Yun; Cong, Yi-Yan; Hu, Guang-Wan; Peng, Shuai; Wang, Qing-Feng (Phytotaxa, 2026)
Impatiens zayuensis (Balsaminaceae), from Cibagou National Nature Reserve in southeastern Xizang, China, is described. Based on molecular evidence, I. zayuensis is assigned to I. sect. Racemosae. Morphologically, it is close to I. margaritifera and I. casseabriae in having spurless flowers, but differs in upper stem with glands, ovate lateral sepals, dentate margin of lateral sepals, sub-dolabriform or oblong lower petal, and oblique mouth of lower sepal. Phylogenetically, the new species does not cluster with the other two similar spurless species, indicating that the spurless character may have evolved several times within the I. sect. Racemosae.